Balanço energético e avaliação econômica de um sistema fotovoltaico para uma indústria de processamento e armazenamento de pescados - Zucareli, Vitor Leandro (2024)
This study addressed the economic viability of a solar plant in a fish processing industry in Assis Chateaubriand/PR, as well as evaluating the energy balance of the product storage process. Using economic indices such as NPV, PBD, and LCOE as per Gitman (2010) and Branker (2011), it investigated the adoption of solar energy to meet the industry's energy needs. The data included solar energy production, plant consumption, and implementation costs. The energy balance, following Risoud's (1999) methodology, considered all forms of energy input and output in fish storage. The results indicated an NPV of R$ 192,846.77, LCOE of 0.70 R$/kWh, and PBD of 11 years. The energy balance resulted in 48,598.54 kWh or 1.25 kWh/kg, with an energy efficiency of 758%. The analyses provided a comprehensive understanding of the system's economic viability and the net energy value of the final product